1997
DOI: 10.2307/3579438
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Instability in Chinese Hamster Cells after Exposure to X Rays or Alpha Particles of Different Mean Linear Energy Transfer

Abstract: Evidence has accumulated that radiation induces a transmissible persistent destabilization of the genome, which may result in effects arising in the progeny of irradiated but surviving cells. An enhanced death rate among the progeny of cells surviving irradiation persists for many generations in the form of a reduced plating efficiency. Such delayed reproductive death is correlated with an increased occurrence of micronuclei. Since it has been suggested that radiation-induced chromosomal instability might depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Whether by radiation or chemical mechanism, DU-UO22+ exposure is consistent with the generally accepted features associated with neoplastic transformation of cells by radiation or metal exposure including formation of sister chromatid exchanges (31,36,37) and genomic instability manifested as gene alterations (6,36,38).…”
Section: Discussionsupporting
confidence: 81%
“…Whether by radiation or chemical mechanism, DU-UO22+ exposure is consistent with the generally accepted features associated with neoplastic transformation of cells by radiation or metal exposure including formation of sister chromatid exchanges (31,36,37) and genomic instability manifested as gene alterations (6,36,38).…”
Section: Discussionsupporting
confidence: 81%
“…It has also been observed that genomic instability leading to genetic alteration can be produced by cytoplasm or membrane irradiation [68]. The possibility of bystander effects has also been raised [69,70].…”
Section: Cytoplasm and Bystander Effectsmentioning
confidence: 99%
“…These studies are based on the premise that the bulk of DNA strand breaks induced by moderate IR doses is repaired within a few minutes or hours after IR exposure [Rogakou et al, 1999]. However, studies performed on delayed IR effects demonstrate that irradiated cells present persistent biological alterations [Jamali and Trott, 1996;Lyng et al, 1996;Manti et al, 1997]. These findings raise questions about long-term, delayed, or late consequences due to persistent DNA lesions or mutations, and the extent to which transcriptional alterations may impose a risk to humans [Falt et al, 2003;Snyder and Morgan, 2004].…”
Section: Discussionmentioning
confidence: 88%